2019
DOI: 10.1002/aocs.12224
|View full text |Cite
|
Sign up to set email alerts
|

Carnauba Wax Particles: Investigation of Dripping and Cold‐Extrusion Processes

Abstract: Solid lipids are commonly used as carrier systems for encapsulation processes. However, formulations containing only solid lipids tend to form a highly ordered crystal lattice, which can expel the active compound during long-term storage, due to the dynamics of polymorphic transitions. Regarding the aspects of particle production, the cooling step of the melted lipid is essential for determining the type of formed crystals. This work aimed to analyze the effects of the crystallization step on the physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Previously, the melting curves of the hollow solid lipid particles formed from fully hydrogenated soybean using SC‐CO 2 were different than the fully hydrogenated soybean oil (Yang & Ciftci, 2016a). It was reported that the melting point of the CW particles formed by the dripping method was same as the original wax (Paulo et al, 2019). As expected, CW samples showed melting peaks with higher enthalpies because of their relatively inert and stable components (de Freitas et al, 2019).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previously, the melting curves of the hollow solid lipid particles formed from fully hydrogenated soybean using SC‐CO 2 were different than the fully hydrogenated soybean oil (Yang & Ciftci, 2016a). It was reported that the melting point of the CW particles formed by the dripping method was same as the original wax (Paulo et al, 2019). As expected, CW samples showed melting peaks with higher enthalpies because of their relatively inert and stable components (de Freitas et al, 2019).…”
Section: Resultsmentioning
confidence: 91%
“…Previously different particles, such as TiO 2 nanoparticles, fully hydrogenated soybean oil microparticles and nanoparticles, and drug nanoparticles were formed using different supercritical particle formation techniques (Padrela et al, 2018; Wu et al, 2008; Yang & Ciftci, 2016a). In the scope of wax particles, Paulo et al (2019) formed CW particles by dripping and cold‐extrusion processes, and Milanovic et al (2010) reported CW particles that were used to encapsulate flavor for food and feed formulations. Also, the production and characterization of solid lipid nanoparticles from CW for drug delivery systems using the microemulsion technique were reported before (Kheradmandnia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, different wall materials, including EOs, configure other release profiles in the medium (Paulo et al, 2019). Under this bias, studies such as that by No et al (2002) reported that chitosan acetate showed a more substantial antibacterial effect against Gram-positive bacteria than against Gram-negative ones, probably due to differences in the structure of the wall of microorganisms that may facilitate or hinder the entry of the substance into the cell.…”
Section: Determination Of Mic and Mbc Using Gelatin And Chitosan Micr...mentioning
confidence: 99%